DuraSeal Exact Is a Safe Adjunctive Treatment for Durotomy in Spine: Postapproval Study. Issue 3 (May 2019) - Kim, Kee D.; Ramanathan, Dinesh; Highsmith, Jason; Lavelle, William; Gerszten, Peter; Vale, Fernando; Wright, Neill
Study Design: A nonrandomized, two-armed prospective study. Objective: Water-tight dural closure is paramount to the prevention of cerebrospinal fluid (CSF) leakage and associated complications. Synthetic polyethylene glycol (PEG) hydrogel has been used as an adjunct to sutured dural repair; however, its expansion postoperatively is a concern for neurological complications. A low-swell formulation of PEG sealant was introduced as DuraSeal Exact Spine Sealant System (DESS). A Post-Approval Study was performed primarily to evaluate the safety and efficacy of DESS for spinal dural repair compared to current alternatives, in a large patient population, reflecting a real-world practice. Methods: A total of 36 sites in the United States enrolled 429 patients treated with DESS as an adjunct to dural repair in the spinal sealant group and 406 patients treated with all other modalities in the control arm, from October 2011 to June 2016. The primary endpoint was the incidence of CSF leak within 90 days of operation. The secondary endpoints evaluated were deep surgical site infection and neurological serious adverse events. Results: The CSF leakage in the DESS group (6.6%) was not significantly different from the control group (6.5%) ( p = .83), and there was no significant difference in the time to first leak. The two groups had no significant differences in deep surgical site infection (1.6% versus control 2.1%, p = .61) or proportion of subjects with neurological serious adverse events (2.9% versus control 1.6%, p = .516). Conclusions: DuraSeal Exact Spinal Sealant is safe when compared to current alternatives for spinal dural repair.